2021
DOI: 10.1002/smll.202100655
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on the Scanning Tunneling Microscopy and Spectroscopy Study of Semiconductor Heterojunctions

Abstract: The band alignment, interface states, interface coupling, and carrier transport of semiconductor heterojunctions (SHs) need to be well understood for the design and fabrication of various important semiconductor structures and devices. Scanning tunneling microscopy (STM) with high spatial resolution and scanning tunneling spectroscopy (STS) with high energy resolution are significantly contributing to the understanding on the important properties of SHs. In this work, the recent progress on the use of STM and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 132 publications
0
3
0
Order By: Relevance
“…The need to characterize forces and imaging cellular ultrastructure is only reachable through advanced techniques such as super-resolution fluorescence microscopy coupled to electron microscopes [ 115 ]. STM/STS might evolve in advanced techniques to provide a three-dimensional profile of the surface and local information at the contact point between two different cell regions in a similar fashion to those measurements for semiconductor heterojunctions [ 116 ].…”
Section: Relevance Of Stm Imaging In Biological Applicationsmentioning
confidence: 99%
“…The need to characterize forces and imaging cellular ultrastructure is only reachable through advanced techniques such as super-resolution fluorescence microscopy coupled to electron microscopes [ 115 ]. STM/STS might evolve in advanced techniques to provide a three-dimensional profile of the surface and local information at the contact point between two different cell regions in a similar fashion to those measurements for semiconductor heterojunctions [ 116 ].…”
Section: Relevance Of Stm Imaging In Biological Applicationsmentioning
confidence: 99%
“…In this connection, we focus especially on the influence of local variations, that is, the specific topography and the different electronic properties of the two substrate regions, G free /S and G bond /S. The results are gained with well-established STM and STS methods revealing electronic properties at well-defined positions on the 2D material surface. , These insights are additionally supported by scanning electron microscopy (SEM), Raman spectroscopy, and atomic force microscopy (AFM).…”
Section: Introductionmentioning
confidence: 99%
“…In this article, the change in charge accumulation layer in the presence of UV is attempted to quantify with scanning tunnelling microscopy (STM). Extensive studies are being reported based on STM to estimate the defect states [5] and band alignment, interface states in heterostructures [6], and the doping concentration [7]. In the memory fields (ReRAM) [8,9].…”
Section: Introductionmentioning
confidence: 99%